ANALISA VARIASI WAKTU FERMENTASI PEMBUATAN BIOETANOL DENGAN BAHAN KULIT SINGKONG DAN KULIT NANAS - Rachmat Subagyo; Wahyu Arifin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2016)
This study studied the best levels of bioethanol from a combination of cassava peel and pineapple peel mixtures with 6 gram yeast mass and 72 hours, 96 hours and 120 hours fermentation time, to determine the optimal fermentation time and find ethanol levels according to SNI. This research was carried out by hydrolysis or cassava peel and pineapple peel using aquades for 30 minute to break the molecule into two parts, then carried out the fermentation process using Saccharomyces Cerevisae (yeast) and the distillation process using a destilator to obtain ethanol for fermentation then tested with a Refractometer to determine whether there is an ethanol level formed from the distillation process. The best sample selected was then tested for ethanol content using the Gas Chromatography tool. The results of this study are known by using the Gas Chromatography tool to determine the ethanol content contained in the distilled sample, the highest ethanol content of each combination. So that the best ethanol yield from a combination of 100% cassava peel - 0% Pineapple Peel with a duration of 120 hours fermentation producing ethanol of 89.81% is still not included in the SNI category.